STRIP-SHAPED DISPLAY STRUCTURE, DISPLAY PANEL AND DISPLAY DEVICE - ZHANG, Enliang; SHI, Haijun; QI, Jiakun; NIU, Hanzhang (2021)
A strip-shaped display structure (10), comprising: a main body portion (11) and an extending portion (12), wherein the main body portion (11) comprises a strip-shaped display portion (110) extending in a first direction and a drive circuit. The strip-shaped display portion (110) comprises a plurality of pixels (1) arranged in an array, wherein each pixel (1) comprises a plurality of color sub-pixels (101/102/103), and each color sub-pixel (101/102/103) comprises a light-emitting device; and the drive circuit is electrically connected to the light-emitting device. The strip-shaped display portion (110) is located at a first end of the main body portion (11), and the extending portion (12) is connected to a second end (22) of the main body portion (11) opposite the first end thereof and is configured to be able to bend from the second end (22) of the main body portion (11) along a bending axis parallel to the first direction so as to be away from a light-emergent side of the light-emitting device. In addition,